Synthesis, Activation, and Characterization of Carbon Fiber Precursor Derived from Jute Fiber - Hossen, Md Shahabul; Islam, Tarikul; Hoque, Sheikh Manjura; Islam, Aminul; Bashar, M. Mahbubul; Bhat, Gajanan (ACS omega, 2024)
Activated carbon (AC) fiber is a carbonaceous material with a porous structure that has a tremendous scope of application in different fields. Conventionally, AC is derived from fossil fuel-based raw materials like polyacrylonitrile (PAN) and pitch. In this work, AC was synthesized from eco-friendly, renewable, and ubiquitous jute fiber. Systematically, the jute fiber was washed and pretreated with NaOH. Raw jute and NaOH-treated jute were carbonized/pyrolyzed at 500 °C for 1 h in presence of N2 gas. The carbonized carbon was activated with H3PO4 and KOH and again pyrolyzed at 650 °C for 1.5 h maintaining the inert condition. The different features of activated carbons were characterized with field emission-scanning electron microscope, energy-dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), X-ray diffraction (XRD), and thermogravimetric analysis. The average yield of carbonized and activated carbons was recorded at 19 and 13.8%, respectively. The scanning electron microscopic images confirmed a honeycomb-like porous structure. It was observed that KOH-activated carbon exhibited a more porous structure than the H3PO4-activated carbons. The average pore diameter of activated carbons was noted to be 1.3 μm. The pore density was higher in case of KOH-activated carbons accounting for 2.15 pore/μm. The EDX analysis showed that H3PO4-activated carbons had more than 90% carbon atoms indicating a significant carbon content. The TEM images revealed that AC particles were in the nanoscale range. The average particle sizes of H3PO4-activated carbon and KOH-activated carbon were 36.38 and 32.8 nm, respectively. The XRD study demonstrated the highly disordered and low level of crystallinity of AC. It was detected that the AC showed much higher thermal resistance than the jute fiber. The H3PO4-activated carbon obtained from NaOH-treated jute remained at 84% even after 500 °C. A higher thermal resistance was achieved with H3PO4-activated carbon since it contains 0.56% phosphorus, which was confirmed by EDX investigation. It was found that a higher carbon yield was obtained from NaOH-treated jute. The porous structure of the material showed that it could be used as an adsorbent. Due to its high thermal stability, it is recommended for flame retardants and heat insulation applications as well.